Effect of Films Thickness on the Surface and Structural Properties of InN Films Grown on Flexible Substrate - Osman, Siti Aisyah; Sha, Shiong Ng; Fong, Kwong Yam (2016)
In this study, indium nitride (InN) thin films were grown on flexible substrate by radio fi·equency reactive sputtering technique. An indium target with purity of99.999% was used. Throughout this work, the RF power and the gas ratio of argon and nitrogen were maintained constant at 60 W and 40:60 (Ar : Nz), respectively. The depositions were carried out at temperature of 300 oc under various deposition thickness. As a result, InN films with various thickness, i.e., 300 nm. 500 nm and 700 nm were produced. Subsequently, the effects of the InN films thickness on th e structural properties and surface morphology were investigated. X-ray diffraction results reveal that wunzite InN thin film s were successfully deposited. It was found that InN tilm with thickness of 700 nm exhibits (I 0 I )-preferred orientation and strongest XRD difhaction peak compared to InN films with thickness of 300 nm and 500 nm. Field emi ss ion scanning electron microsco py and atomic force microscopy results show that all the InN thin films exhibit smooth and uniform surface morphology but the InN grain size increases with increasing film thickness. Howevct·. the root mean square surface roughness of the InN films shows little apparent variations as the film thickness in cr<:ascs. All the findings lead to conclude that the crystalline quality of InN thin films were effectively improved with increasing film thickness.